Isotopically Heavy Micrometeorites—Fragments of CY Chondrite or a New Hydrous Parent Body?. Issue 8 (26th August 2022) - Suttle, M. D.; Folco, L.; Dionnet, Z.; Van Ginneken, M.; Di Rocco, T.; Pack, A.; Scheel, M.; Rotundi, A.
Abstract: Cosmic dust grains sample a diverse range of solar system small bodies. This includes asteroids that are not otherwise represented in our meteorite collections. In this work we obtained 3D images of micrometeorite interiors using tomography before collecting destructive high‐precision oxygen isotope measurements. These data allow us to link textures in unmelted micrometeorites to known chondrite groups. In addition to identifying particles from ordinary chondrites, CR and CM chondrites we report two micrometeorites derived from an anomalous 16 O‐poor source (δ 17 O: +16.4‰, δ 18 O: +28.4‰, and Δ 17 O: +1.4‰). Their compositions overlap with a previously reported micrometeorite (TAM50‐25) from Suttle et al. (2020), https://doi.org/10.1016/j.epsl.2020.116444 (EPSL: 546:116444). These particles represent hydrated carbonaceous chondrite material derived either from a new group or from the CY chondrites (thereby extending the isotopic range of this group). In either scenario they demonstrate close petrographic and isotopic connections to the CO‐CM chondrite clan. Furthermore, their position in O‐isotope space makes them the most likely candidate for the parent body of the anomalous "group 4" cosmic spherules previously reported by Suavet et al. (2010), https://doi.org/10.1016/j.epsl.2010.02.046 (EPSL: 293:313‐320) and several subsequent isotopic studies. We conclude that the "group 4" cosmic spherules originate from hydrated C‐type asteroid parents. Plain Language Summary: One of the principal aims of planetary science is to understand the origin and formation of our solar system. Studying primitive extraterrestrial material found at the Earth's surface allows us to explore the chemical composition of early formed solids which acted as the "building blocks" for planet formation. Most research analyses large (centimeter and bigger) meteorites. Here, we investigated the smaller size fractions (cosmic dust) using a combination of tomography to image particle interiors and destructive mass spectrometry to measure their oxygen isotope compositions. We identify two anomalous particles containing abundant heavy oxygen. These grains are part of the carbonaceous chondrite super group but appear to sample a new and otherwise unstudied group. This discovery is significant because it broadens our awareness of the geological diversity of the asteroid belt and compositional variation that existed among planetesimals in the early solar system. Key Points: Combined bulk O‐isotopes and micro‐CT allow the provenance of cosmic dust grains to be inferred with confidence Particles from a 16 O‐poor source represent either a new group of carbonaceous chondrites or an extension of the CY chondrite range These particles define the pre‐atmospheric O‐isotope composition of a previously reported collection of anomalous cosmic spherules